2012
DOI: 10.1111/j.1467-9248.2012.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Deliberating across Deep Divides

Abstract: Deeply divided societies would seem to be infertile ground for mass deliberation. ‘Enclave deliberation’, among people on the same side, may well occur. But people on opposing sides may not trust one another, they may not listen with an open mind, or they may regard the other side's arguments as insincere cover for sectional interests. Perhaps, though, we underestimate their deliberative capacities? This article examines a deliberative poll (DP) in the Omagh area of Northern Ireland, a society having only rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 14 publications
0
68
0
Order By: Relevance
“…Michael Morrell (2010), in a pioneering study, contends that cognitive empathy (gaining knowledge on the other person's preferences and reasons for that position, juxtaposed against affective empathy which is knowledge of another person's mental state) is driven by reciprocity. Caluwaerts and Reuchamps (2014; see also Luskin, O'Flynn, Fishkin, & Russell, 2014) argue that deliberation acts as a buffer against more negative feelings towards the out-group, and demonstrate this finding in the context of two deliberative experiments in Belgium. These 9 Social learning is a 'group-level change' because it necessitates a dyadic relationship with another agent.…”
Section: Meso-changes: Social Learning Polarization and Consensusmentioning
confidence: 88%
See 1 more Smart Citation
“…Michael Morrell (2010), in a pioneering study, contends that cognitive empathy (gaining knowledge on the other person's preferences and reasons for that position, juxtaposed against affective empathy which is knowledge of another person's mental state) is driven by reciprocity. Caluwaerts and Reuchamps (2014; see also Luskin, O'Flynn, Fishkin, & Russell, 2014) argue that deliberation acts as a buffer against more negative feelings towards the out-group, and demonstrate this finding in the context of two deliberative experiments in Belgium. These 9 Social learning is a 'group-level change' because it necessitates a dyadic relationship with another agent.…”
Section: Meso-changes: Social Learning Polarization and Consensusmentioning
confidence: 88%
“…Undertaking a deliberative poll in Omagh, Northern Ireland, Luskin et al (2014) demonstrated that Catholics and Protestants were able to deliberate meaningfully, gain knowledge of opposing viewpoints, and ultimately support greater intermingling of ideas in policy outputs. Caluwaerts and Ugarriza (2014,), drawing upon nine case studies of divided societies from across the globe, argue that deliberation can lead to conflict resolution when institutions are decentralized (i.e.…”
Section: Macro-changes: Popular Support Deep Divisions and Democratmentioning
confidence: 99%
“…Although processing of evidence is culturally biased as described above, there are limits to the degree to which people can pick the evidence that suits them (Kunda 1990). Furthermore, there is evidence (Vinokur & Burnstein 1978;Luskin et al 2012;Cohen et al 2007) that deliberations between adherents of conflicting worldviews or ideologies brings these people closer together with respect to their factual beliefs. Insofar as the willingness (and perhaps even active desire) to engage with the arguments of political opponents is also a part of the public-reason norm, it has resources to diffuse the kind of conflicts that arise from cultural cognition as well.…”
Section: Deliberationmentioning
confidence: 99%
“…But understanding why they are misplaced can itself add to the legitimacy of a decision (Mill 1991(Mill [1861, 282). It can help people to see more clearly why the decision went one way rather than another, and hence increase their confidence in the epistemic merits of the decision (Cohen 1986;Estlund 2007;Luskin et al 2014). …”
Section: Why Take a Deliberative Approach?mentioning
confidence: 99%